PENGARUH GAYA KEPEMIMPINAN, PENGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PEKERJAAN UMUM DAN PENATAAN RUANG (PUPR) DI GEDUNG A BAGIAN KEUANGAN KOTA BANDA ACEH - muhammad muhammad; Nurbismi Nurbismi; Reza Maulana (SI-MEN, 2022)
Hypothesis testing using multiple linear regression analysis, F test (simultaneous) and t test (partial) is intended to determine the effect of independent variables on dependent variable at the 95% confidence level (u 0*05). The results showed that partially leadership style had an effect on employee performance at the PUPR service office in Banda Aceh City with a t count (9.011) greater than t table (1.69). Partially Supervision has an effect on Employee Performance at the PUPR Service Office of Banda Aceh City with a t count (3.187) greater than t table (1.69). Partially, Work Discipline has an effect on Employee Performance at the PUPR Service Office of Banda Aceh City with a t count (2.840) greater than t table (1.69). Simultaneously Leadership Style, Supervision and Work Discipline simultaneously affect Employee Performance at PUPR service office of Banda Aceh City with F count (56.325) greater than F tabe1 (2.92). Thus it can be concluded that both partially and simultaneously the variables of Leadership Style, Supervision and Work Discipline have a significant effect on Employee Performance at the PUPR service office in Building A, Finance Section, Banda Aceh City.